Firefighters are Heroes of Modern Age - Siniša, Franjić (Journal of Advanced Forensic Sciences, 2020)
Fire is an uncontrolled combustion that causes material damage and endangers human lives. Combustion is a chemical process that causes the oxidation of the fuel constituents of a some kind fuel. It is a process between fuel and oxidants in which heat is generated due to changes in chemical constituents. By releasing heat, it may occur light in the form of annealing or flame. There are accidental and arson fires. This work is dedicated to all firefighters in the world who very often find themselves in situations where they save the lives of others while neglecting their own safety. Firefighters are the heroes of modern times.
Keywords: Fire; Arson; Firefighters; Investigation